2022
DOI: 10.1186/s12916-022-02556-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of baseline arterial stiffness on effects of intensive compared with standard blood pressure control: a post hoc analysis of the STEP trial

Abstract: Background The benefits and risks of intensive versus standard systolic blood pressure (SBP) treatment in older patients with arterial stiffness (AS) remains unclear. This study aims to investigate the interaction between the baseline AS and SBP treatments on cardiovascular outcomes. Methods In this post hoc analysis of the Strategy of Blood Pressure Intervention in the Elderly Hypertensive Patients (STEP) trial, we involved 6865 participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is controlled by elements coming from various levels of the vessel wall as well as chemicals like insulin and aldosterone in plasma [24]. Studies have shown that CIMT is mainly used as a measure of localized vascular lesions, whereas baPWV is currently used as a measure of AS [25][26][27]. A study by Amparo et al that included 415 European Americans with an average age of 55 years old confirmed that VFA was independently associated with increased AS and was an independent predictor of CVD, while SFA and BMI did not predict CVD [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is controlled by elements coming from various levels of the vessel wall as well as chemicals like insulin and aldosterone in plasma [24]. Studies have shown that CIMT is mainly used as a measure of localized vascular lesions, whereas baPWV is currently used as a measure of AS [25][26][27]. A study by Amparo et al that included 415 European Americans with an average age of 55 years old confirmed that VFA was independently associated with increased AS and was an independent predictor of CVD, while SFA and BMI did not predict CVD [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a multicenter observational study had proved that elevated baPWV mediates a positive correlation between aging and blood pressure, indicating AS might precede increased blood pressure 7 . Another clinical trial had discovered that patients with AS (baPWV≥1800cm/s) at baseline were significantly less likely to achieve their target SBP than those without AS, verifying AS consistently preceded SBP 20, 21 . Additionally, a large-scale cohort based on general Chinese population demonstrated that baPWV had a higher predictive value of ASCVD and all-cause mortality versus blood pressure 22 .…”
Section: Discussionmentioning
confidence: 99%